Tuning Cancer Fate: Tumor Microenvironment's Role in Cancer Stem Cell Quiescence and Reawakening - Sistigu, Antonella; Musella, Martina; Galassi, Claudia; Vitale, Ilio; De Maria, Ruggero (Frontiers in Immunology, 2020)
Cancer cell dormancy is a common feature of human tumors and represents a major clinical barrier to the long-term efficacy of anticancer therapies. Dormant cancer cells, either in primary tumors or disseminated in secondary organs, may reawaken and relapse into more aggressive disease. The mechanisms underpinning dormancy entry and exit strongly resemble those governing cancer cell stemness, and include intrinsic and contextual cues. Cellular and molecular components of the tumor microenvironment persistently interact with cancer cells. This dialog is highly dynamic, as it evolves over time and space, strongly cooperates with cell intrinsic nets, and governs cancer cell features (like quiescence and stemness) and fate (survival and outgrowth). Therefore, deeper insights into the biology of dormant cancer (stem) cells and the mechanisms regulating the equilibrium quiescence-versus-proliferation are vital in our pursuit to find new therapeutic opportunities that prevent cancer from ever recurring. Here, we review and discuss microenvironmental regulations of cancer dormancy and its parallels with cancer stemness, as we offer a view of the therapeutic strategies adopted to prevent lethal recurrence, by either eradicating resident dormant cancer (stem) cells or maintaining them in a dormant state